Factors influencing unemployment among fresh graduates of UiTM in Southern Part of Malaysia / Adlin Sofiya Zamrud - Zamrud, Adlin Sofiya (Faculty of Business and Management, 2020)
One of the main issues being discussed by academics in higher education is the graduate unemployment rate. College and university students often face unemployment after investing their precious money and time in order to receive educational benefits. It puts them at risk to unfavourable economic performance when those students have spent a lot of their resources on higher education. This paper examines the factors that causing unemployment among Universiti Teknologi Mara (UiTM) fresh graduates in southern part of Malaysia. 99 data from the respondents was collected and analyzed using SPSS version 22. There are several factors explaining their status as unemployed and this paper identifies each component at an individual level. This paper provides direction for further research with specific analysis of the phenomena of unemployment. This paper found that graduates attributes and job mismatch are the reasons of unemployment among fresh graduates of UiTM in southern part of Malaysia.